Choline-related metabolites influenced by feeding patterns in preterm and term infants. (17th January 2020) - Shoji, Hiromichi; Taka, Hikari; Kaga, Naoko; Ikeda, Naho; Hisata, Ken; Miura, Yoshiki; Shimizu, Toshiaki
Abstract: Objective : This study was performed to examine the choline status on term and preterm infants using urinary metabolome analysis. Material and methods: Samples were collected from 19 term and 20 preterm infants between 15 days and 1 month, respectively. The infants were separated into four groups: the term-breast group (TB, n = 13), the term-formula group (TF, n = 6), the preterm-breast (PB, n = 11), and the preterm-mixed group (PM, n = 9). Urinary metabolome analysis was performed using capillary electrophoresis–time-of-flight mass spectrometry (CE–TOF/MS). We also performed metabolome analysis of the infant formulas. Results: Urinary excretion of choline metabolites (choline, N, N -dimethylglycine, sarcosine, and betaine) was significantly higher in TB than TF infants ( p < .05). Choline, betaine, and sarcosine excretion was not significantly different between the PB and TB infants. Choline and N, N -dimethylglycine excretion was significantly higher in PM than PB infants. Choline metabolites excretion was also significantly higher in PM than TF infants. Choline and betaine levels were significantly higher in the preterm than term formula used in this study. Conclusions: The type of feeding in early infancy affects choline metabolism. Metabolome analysis is useful for assessing choline metabolism to modify the contents of infant formulas also in preterm infants.